APPLYING THE STORY TELLING METHOD TO IMPROVE PUBLIC SPEAKING SKILL FOR ENGLISH STUDENTS - Linda Safitri; Akbar Jaya; Jana Siti Nor Khasanah (Universitas Duta Bangsa Surakarta, 2023)
This research aims to find out whether or not and what extent storytelling can improve the public speaking skill for English students. This research is classroom action research. They are 4 procedures those are planning, action, observation and reflecting. The data are in the form of qualitative and quantitative. The quantitative data were taken from the test conducted before and after the actions were implemented then the qualitative data were taken from the result of observation while the actions were being carried out. The data in this research are English students at Islamic University Jayapura. Based on the analysis of data, the researcher finds that the storytelling method can improve the public speaking skill for English students. Students became more active, confidence and enthusiastic. The mean score for 1st semester pre test 70.96 increased to 84.16 in post- test 2 and 3rd semester pre test 76.4 increased to 84.5 in post-test 2.